2003
DOI: 10.1016/s0022-5223(03)00607-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac surgery during pregnancy: pulsatile or nonpulsatile perfusion?

Abstract: Cardiopulmonary bypass (CPB) during pregnancy is associated with a high fetal and maternal mortality. Contributing factors are timing of the operation, emergency situations, and placental vasoconstriction. Experimental evidence suggests that pulsatile perfusion might prevent placental vasoconstriction. We report on 4 patients who underwent cardiac surgery during pregnancy with pulsatile perfusion and detailed fetal monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Thus, as remarked by Mr. Jahangiri, full maternal and fetal monitoring is critical for improving outcomes [3].In our study, a 33-year-old pregnant woman with Marfan syndrome and her fetus (26 weeks of gestation) died after surgical treatment of acute type A aortic dissection. At the time of the patient's presentation, we counseled the patient regarding the high risk of fetal loss if the procedure was performed with the fetus remaining in situ with deep hypothermia and circulatory arrest.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…Thus, as remarked by Mr. Jahangiri, full maternal and fetal monitoring is critical for improving outcomes [3].In our study, a 33-year-old pregnant woman with Marfan syndrome and her fetus (26 weeks of gestation) died after surgical treatment of acute type A aortic dissection. At the time of the patient's presentation, we counseled the patient regarding the high risk of fetal loss if the procedure was performed with the fetus remaining in situ with deep hypothermia and circulatory arrest.…”
mentioning
confidence: 65%
“…Thus, as remarked by Mr. Jahangiri, full maternal and fetal monitoring is critical for improving outcomes [3].…”
mentioning
confidence: 99%
“…8 Maintaining adequate placental circulation seems to be the key to safe surgery. 9 Jahangiri et al 10 reported the usefulness of pulsatile CPB in cardiac surgery during pregnancy. We used an intra-aortic balloon pump during CPB to maintain pulsatile fl ow in our patient and monitored the fetal heartbeat during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The bradycardia often appears at the beginning of CPB in the event of hypoxia, secondary to decreased fetal oxygenation, placental hypotension, or acid-base imbalance, and can persist for the total duration of CPB but may be reversible by increasing perfusion flow [9]. Fetal bradycardia and demise may also be attributable to the use of nonpulsatile perfusion [98]. In addition, uterine contractions are particularly common during the rewarming phase after moderate or profound hypothermia [99].…”
Section: Feto-neonatal Outcomesmentioning
confidence: 99%
“…Accordingly, the reliability of nonpulsatile normothermic CPB has been questioned and whether it can meet the needs of fetoplacental circulation. Tocodynamometer monitoring appears imperative to obtain sufficient information about the uterus to intervene where necessary [98]. Cesarean section after heparinization and cannulation of the mother before the start of CPB is another alternative to improve fetal outcome [17].…”
Section: Feto-neonatal Outcomesmentioning
confidence: 99%